SOCIAL MEDIA AND THE INCIDENCE OF CYBERBULLYING IN NIGERIA: IMPLICATIONS FOR CREATING A SAFER ONLINE ENVIRONMENT - Nofisat Akeusola , Bolanle (Al-Ijtima`i: International Journal of Government and Social Science, 2023)
Social media has become an integral part of communication and information sharing worldwide, including Nigeria. However, despite its benefits, social media platforms also pose risks, with cyberbullying emerging as a prevalent and concerning issue. This article reviews incidence, forms, consequences, and approaches to promoting safer online environments in Nigeria. Using a qualitative research design, a comprehensive literature review and thematic analysis of secondary sources were conducted. The findings revealed that cyberbullying is prevalent in Nigeria and exists in various forms such as outing, trickery, trolling, and verbal and visual/sexual cyberbullying. Meanwhile, the phenomenon has negative emotional and psychological consequences. The review highlights the lack of awareness and understanding of cyberbullying among stakeholders, leading to the underestimation and underreporting of incidents. This emphasizes the need for specific policies and comprehensive preventive measures. While the current legislation addresses certain aspects of cyberbullying, a dedicated policy on cyberbullying management is lacking. To promote safer online environments, this study suggests involving various stakeholders and developing tailored prevention and intervention strategies. This includes educating students and staff on cyberbullying, implementing reporting mechanisms, and providing support systems. Further research is needed to explore the role of social media platforms in cyberbullying experiences, involvement of technology companies and stakeholders, and effective strategies for prevention and intervention.